The distribution of the thermally tolerant symbiont lineage (Symbiodinium clade D) in corals from Hawaii: correlations with host and the history of ocean thermal stress - Stat, Michael (Blackwell Publishing Ltd, 2013)
Spatially intimate symbioses, such as those between scleractinian corals and unicellular algae belonging to the genus Symbiodinium, can potentially adapt to changes in the environment by altering the taxonomic composition of their endosymbiont communities. We quantified the spatial relationship between the cumulative frequency of thermal stress anomalies (TSAs) and the taxonomic composition of Symbiodinium in the corals Montipora capitata, Porites lobata, and Porites compressa across the Hawaiian archipelago. Specifically, we investigated whether thermally tolerant clade D Symbiodinium was in greater abundance in corals from sites with high frequencies of TSAs. We recovered 2305 Symbiodinium ITS2 sequences from 242 coral colonies in lagoonal reef habitats at Pearl and Hermes Atoll, French Frigate Shoals, and Kaneohe Bay, Oahu in 2007. Sequences were grouped into 26 operational taxonomic units (OTUs) with 12 OTUs associated with Montipora and 21 with Porites. Both coral genera associated with Symbiodinium in clade C, and these co-occurred with clade D in M. capitata and clade G in P. lobata. The latter represents the first report of clade G Symbiodinium in P. lobata. In M. capitata (but not Porites spp.), there was a significant correlation between the presence of Symbiodinium in clade D and a thermal history characterized by high cumulative frequency of TSAs. The endogenous community composition of Symbiodinium and an association with clade D symbionts after long-term thermal disturbance appear strongly dependent on the taxa of the coral host.